The Reality of Professional Self-Development and Its Obstacles for High School Female Teachers in Riyadh from Their Point of View - Alenzi, Abeer Mousa (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the reality of the professional self-development of secondary school female teachers in Riyadh and the obstacles to professional self-development from their point of view with an indication of the effect of the variables (academic qualification, years of experience) in that. The study relied on the descriptive approach- survey, and used the questionnaire tool. The study was applied to a random sample consisting of (260) secondary school female teachers in Riyadh. The study reached the following results: The axis of the reality of professional self-development got an average (4.14 out of 5) with a degree (high), and the axis of obstacles to professional self-development got an average (3.98 out of 5), meaning the obstacles were represented by a (large) degree. The results also revealed that there are no differences between the viewpoints of the study sample due to the two variables (academic qualification and years of experience). Based on the results, the researcher made a number of necessary recommendations to avoid obstacles to the professional self-development of secondary school female teachers.